Water crisis in São Paulo in 2014: drought and deforestation - Marengo, Jose Antonio; Alves, Lincoln M (GEOUSP Espaço e Tempo (Online), 2015)
This study shows an hydrometeorological analyses of the 2013-2014 rainy season in Southeastern Brazil, in order to assess the magnitude and extension of the drought and water crises that affect the State of Sao Paulo during summer of 2014. For that we analyze mean rainfall and anomalies during the peak rainfall months (December-February). In particular, rainfall was well below normal from December 2013 to February 2014. We investigate the physical causes of this lack of rain in the region, in the context of rain producing mechanisms in the region, including the role of the Amazon tropical rainforest as one of the sources or moisture for rainfall in Southern and Southeastern Brazil. Rainfall analyses showed that summertime accumulated were about 62% below normal in 2014, and together with a 2,5 oC warmer summer and increase in water use, all of these generated an unprecedented water crisis since 1960.